Ownership concentration and bank performance: Evidence from India - Neeraj Gupta; Sachin Mittal; Tarun Agarwal; Priti Bakhshi; Minati Sahoo (Cogent Economics & Finance, 2022)
The purpose of this study is to examine the impact of ownership concentration on the performance of Indian commercial banks. A panel data approach has been used in this study. Particularly, the effect estimation and GMM has been used in this study to examine the relationship between ownership concentration and bank performance during 2009-2010 to 2018-2019. The findings reveal that the largest shareholder impacts the bank's performance positively. The results are robust across the various proxies of bank performance, and sub-samples based on ownership and size of the bank. The present study may be useful for Indian banking regulators and investors to understand the impact of ownership concentration on bank performance.
Keywords: 330; bank; ownership; performance; public sector banks; private sector banks